Os Acordos de Basileia I, II, III e o mercado bancário brasileiro: um estudo sobre os principais desafios da gestão de liquidez nesse novo cenário - Cunha, Marina Martins Brito da (2014)
During the banking history, there were movements of changes and adaptation to new realities, such as the internationalization and the increasing globalization of the financial markets. In this process economic instabilities of national monetary systems were recorded which raised questions about the necessity of strengthening the international monetary system and the stability of financial institutions of the countries. Amid the market turbulence , the Bank For International Settlements (BIS), has created the Basel Committee of Banking Supervision Basel that promulgated the Basel Accord entering the principles of banking supervision and a system for measuring and standardizing minimum capital requirements, in an attempt to manage the risks. This paper aims to analyze the effects of the implementation of Basel Accords on the structure and operation of the Brazilian financial system. The analysis method adopted is based on the historical and documentary evaluation of the Basel Accords I, II and III in the the Brazilian financial system, analyzing the principles of banking supervision and regulation implemented by the Brazilian Central Bank and financial institutions, such as the regulation of minimum capital and net worth, through Resolution No. 2099 and its main changes. The paper also provides an analysis of the new capital agreement with its main characteristics. Its implementation occurred through the Statement N. 12.746 of 2004, when the Brazilian Central Bank set a timetable to be followed by financial institutions for the implementation of several improvements in risk management controls and also the role of supervision and information disclosure to the financial market.Through the Statement N. 20.615 of 2011, a new step was taken to improve the inclusion of Basel III, one of the points presented was the improvement in the liquidity risk management. The paper concluded that despite of many improvements have been still discussed and have been under implementation in the Brazil and in the international markets, these innovations initiated by the Basel Accord marked the history of management and supervision of risk management in the financial market